KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS BERITA DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 18 PADANG - Fanno, Bimma Geo; Afnita, Afnita (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research there are three. First, it describes the skills of reading comprehension text news grade VIII SMP Negeri Padang 18. Second, the governing text news writing skills of students of class VIII SMP Negeri Padang 18. Third, to analyze the correlation between the skills of reading comprehension texts with news writing skills text news grade VIII SMP Negeri Padang 18. Type of this research is a descriptive method quantitative research. The research design used was the korelasional relationship of two variables. The population of this research grade VIII SMP Negeri Padang 18 listed on the 2018/2019 school year with a total of 168 students scattered in five classes. The sample in this study amounted to 40 people. Sample taken using a simple random technique with a precision of 15% using simple random sampling. Research instrument this is a test performance, namely, test write text news and objective tests the skills of reading comprehension text news. Based on the data analysis and discussion, obtained three of the following. First, the skills of reading comprehension text news grade VIII SMP Negeri Padang is at 18 qualifying well. It is inferred based on the average count of 82.56. Secondly, the text of the news writing skills of students of class VIII SMP Negeri 18 are on good qualification. This can be seen from the average earnings to calculate a test write text news of 79.17. Third, there is a significant relationship between the relationship skills reading comprehension texts with news writing skills text news have a relationship on a significant level 95% with dk = n-1. Based on test-t accepted hypothesis, because thitung > t table i.e. 2,509 > 1.68.Â Kata kunci: Membaca Pemahaman, Teks Berita